Gas-phase chemistry in space : from elementary particles to complex organic molecules - Lique, François; Faure, Alexandre (IOP (Series). Release 5., 2019)
Gas-Phase Chemistry in Space: From elementary particles to complex organic molecules is written by a collection of experts in the field of astrochemistry. The book introduces essential concepts that govern the formation, excitation and destruction of molecules at a postgraduate and research level. A broad range of topics are covered; from early universe chemistry and stellar nucleosynthesis, to the study of bimolecular reaction kinetics. Detailed description of the gas-phase process is provided and recent examples of the interplay between observational and laboratory astrophysics are examined. Using more than 100 figures, as well as examples, this work reveals, in detail, both theoretical and experimental perspectives that can be implemented in future discoveries.